Spectrum of Obstetrics ase Referrals - Ghimire, Asmita; Shrestha, Reshika; Yadav, Jeshika; Thapaliya, Ishwor; Sapkota, Sangrila; Khatiwoda, Susmita; Ojha, Neebha (Journal of Nepal Health Research Council, 2025)
Background: Maternal health is an important focus for ensuring the well-being of both mothers and their babies. Maternal and fetal mortality which is a burning issue especially in third world countries can be reduced significantly with right obstetric referral. This study reviewed the primary reasons, time, distance, and pattern of obstetric cases referred to a tertiary center.Methods: This descriptive study was conducted after taking ethical approval {Approval number 136 (6-11) E2} from the review board of Maharajgunj Medical Campus, Nepal, and data of three years from 1st August 2020- 31st September 2023 were analyzed from medical records. The study included all referral cases aged 18-45 years who were past 28 weeks of gestation till 42 days post-delivery. Women who had incomplete medical records were excluded from the study. A continuous convenience sampling method was used. The point estimate was calculated at a 95% confidence interval.Results: Among 174 referred cases, 84 (48.28%) were from the government district-level hospitals with the predominant reason being medical disorders complicating pregnancy 136 (78.17%). The majority of cases 94 (54.02%) were referred during the intrapartum period.Conclusions: Medical disorders complicating pregnancy were the primary cause for the referral in obstetrics cases, notably from district-level hospitals having less manpower to deal with those cases. Keywords: Hospital; maternal mortality; obstetric; pregnancy; referrals.